The status of social studies : views from the field - Passe, Jeff (Emerald Publishing Limited : Information Age Publishing, 2013)
A team of researchers from 35 states across the country developed a survey designed to create a snapshot of social studies teaching and learning in the United States. With over 12,000 responses, it is the largest survey of social studies teachers in over three decades. We asked teachers about their curricular goals, their methods of instruction, their use of technology, and the way they address the needs of English language learners and students with disabilities. We gathered demographic data too, along with inquiries about the teachers' training, their professional development experiences, and even whether they serve as coaches.The enormous data set from this project was analyzed by multiple research teams, each with its own chapter. This volume would be a valuable resource for any professor, doctoral student, or Master's student examining the field of social studies education.It is hard to imagine a research study, topical article, or professional development session concerning social studies that would not quote findings from this book about the current status of social studies. With chapters on such key issues as the teaching of history, how teachers address religion, social studies teachers' use of technology, and how teachers adapt their instruction for students with disabilities or for English language learners, the book's content will immediately be relevant and useful.